Parametrized post-Friedmannian framework for interacting dark energy theories - Skordis, C.; Pourtsidou, A.; Copeland, Edmund J. (American Physical Society, 2015)
We present the most general parametrization of models of dark energy in the form of a scalar field which is explicitly coupled to dark matter. We follow and extend the parametrized post-Friedmannian approach, previously applied to modified gravity theories, in order to include interacting dark energy. We demonstrate its use through a number of worked examples and show how the initially large parameter space of free functions can be significantly reduced and constrained to include only a few nonzero coefficients. This paves the way for a model-independent approach to classify and test interacting dark energy theories.